Upper Jurassic (Tithonian) belemnites from the Neuquén Basin, Argentina. (April 2023) - Vennari, Verónica V.; Aguirre-Urreta, Beatriz; Marin, Luciana S.; Pellenard, Pierre; Martinez, Mathieu; Tunik, Maisa
Abstract: Belemnites were a group of Mesozoic coleoids with a global distribution from the Early Jurassic to the Late Cretaceous. During the Late Jurassic–Early Cretaceous, Gondwana's marine shelves were dominated by Belemnopsis and Hibolithes populations. In contrast to the Austral Basin, where both genera are quite common, their record in the Neuquén Basin (Argentina) is rather scarce and poor, probably due to a combination of locally unfavorable environmental conditions and predation pressure. Here we describe a new belemnite association from the Tithonian of the Vaca Muerta Formation from southern Mendoza and northern Neuquén provinces. Belemnite's findings are assignable to the Tithonian Windhauseniceras internispinosum and Corongoceras alternans Andean ammonoid Biozones. The studied rostra are identified as Belemnopsis cf. B. patagoniensis, Belemnopsis cf. B. launceloti, and Hibolithes argentinus ? Affinities of the Neuquén Basin belemnite fauna are referred to the Madagascan-Eastern Africa associations (Ethiopian Subprovince, Tethyan Province), adding evidence to an established Trans-Gondwana seaway enabling the connection between those areas from the Tithonian onwards. Highlights: New Tithonian belemnite data from the Neuquén Basin, western Argentina. 21 Belemnites are assigned to the genera Belemnopsis and Hibolithes. The belemnite association is close to Madagascan-Eastern African faunas. The studied belemnite fauna add new evidence supporting an open Trans-Gondwana seaway from the Tithonian onwards.